ANALISIS FENOMENA PASANGAN CALON TUNGGAL DALAM PEMILIHAN KEPALA DAERAH DI KABUPATEN GROBOGAN TAHUN 2020 - Teguh Ilham; Riky Fajar Sujatmiko (Jurnal Ilmiah Wahana Bhakti Praja, 2022)
It has been calculated that 53 regions have held regional head elections with a single candidate pair until 2020. Grobogan Regency is one of them. The author focuses on the problem of the emergence of the phenomenon of single candidate pairs in Grobogan Regency. The purpose of this study is to analyze the implementation of regional head elections and the factors causing the emergence of a single candidate pair in the regional head election in Grobogan Regency in 2020. The method used in this paper is a descriptive method with an inductive approach. This study found the personal strength of the incumbent, restrictions for members of the legislature and civil servants to nominate themselves as regional heads, high political costs, and reduction in the term of office of regional heads causing the emergence of a single candidate pair. In order to anticipate the reappearance of this phenomenon, it is recommended that political parties maximize their recruitment function and revise the Law on the election of regional heads and the State Civil Apparatus.